Safety and efficacy of lenvatinib combined with camrelizumab plus transcatheter arterial chemoembolization for unresectable hepatocellular carcinoma: A two-center retrospective study - Sun, Bo; Zhang, Lijie; Sun, Tao; Ren, Yanqiao; Cao, Yanyan; Zhang, Weihua; Zhu, Licheng; Guo, Yusheng; Gui, Yuxi; Liu, Fengyong; Chen, Lei; Xiong, Fu; et al. (Frontiers in Oncology, 2022)
Abstract Objectives: To compare the safety and efficacy of lenvatinib (LEN) combined with camrelizumab plus transcatheter arterial chemoembolization (TACE-LEN-C) and TACE combined with LEN (TACE-LEN) in patients with unresectable hepatocellular carcinoma (uHCC). Methods: Eighty-three patients with uHCC treated with TACE-LEN-C or TACE-LEN from September 2018 to May 2021 were enrolled in this retrospective study. Overall survival (OS), progression-free survival (PFS), local tumor response, and adverse events (AEs) were evaluated. Univariate and multivariate analyses were used to determine the factors affecting survival. Results: There were 31 patients in the TACE-LEN-C group and 52 patients in the TACE-LEN group. The median follow-up period was 14.2 months (range 7.2–25.2 months) in the whole study. The combination of triple therapy was found to significantly prolong the PFS (12.5 months vs. 6.6 months, P<0.001) and OS（18.9 months vs. 13.9 months, P<0.001. In terms of tumor response, the combination demonstrated a higher objective response rate (71% vs. 42.3% by the modified Response Evaluation Criteria in Solid Tumors, P=0.023) without a statistically significant difference in the disease control rate (93.5% in TACE-LEN-C, 80.8% in TACE-LEN, P=0.195). In the multivariate analysis, two independent factors affecting PFS were identified: number of tumors and treatment. Three independent factors affected OS: number of tumors, Barcelona Clinic Liver Cancer (BCLC) stage, and treatment. All the AEs were tolerable. Conclusion: TACE-LEN-C is a safe and effective treatment for patients with uHCC, and could be a potential treatment option.